2005
DOI: 10.1073/pnas.0508649102
|View full text |Cite
|
Sign up to set email alerts
|

A data integration methodology for systems biology: Experimental verification

Abstract: The integration of data from multiple global assays is essential to understanding dynamic spatiotemporal interactions within cells. In a companion paper, we reported a data integration methodology, designated Pointillist, that can handle multiple data types from technologies with different noise characteristics. Here we demonstrate its application to the integration of 18 data sets relating to galactose utilization in yeast. These data include global changes in mRNA and protein abundance, genome-wide protein-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 34 publications
1
86
0
Order By: Relevance
“…The applicability of our methodology to different types and sizes of data and to different numbers of data sets is demonstrated by application to five different types of data integration in a companion paper (10). Although we focused here on presenting our methodology from the perspective of maximizing statistical power, it can also be applied to scenarios for which the different types of data being integrated have systematic differences between them, for example, combining mRNA and protein abundance measurements or in vivo and in vitro measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of our methodology to different types and sizes of data and to different numbers of data sets is demonstrated by application to five different types of data integration in a companion paper (10). Although we focused here on presenting our methodology from the perspective of maximizing statistical power, it can also be applied to scenarios for which the different types of data being integrated have systematic differences between them, for example, combining mRNA and protein abundance measurements or in vivo and in vitro measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Although we focused here on presenting our methodology from the perspective of maximizing statistical power, it can also be applied to scenarios for which the different types of data being integrated have systematic differences between them, for example, combining mRNA and protein abundance measurements or in vivo and in vitro measurements. Examples of this type of integration are given in the companion paper (10). Data integration can never rule out inclusion of some false positives or loss of some true positives.…”
Section: Discussionmentioning
confidence: 99%
“…There are three main categories to construct biomolecular regulatory networks: gene regulatory networks through a mathematical model; networks through literature mining, and integrating multiple data (Friedman et al, 2000;Hwang et al, 2005;Mohamed-Hussein and Harun, 2009). Building a network through literature mining means using bioinformatics, computational biology, and other tools of computer science to analyze the data in the literature, and build biomolecular regulatory networks using the relationships between gene/protein interactions of the existing literature.…”
Section: A B Discussionmentioning
confidence: 99%
“…Hwang et al (2005a) have also recognized the issues in data integration, when the different data types vary in size, confidence, and network coverage and have developed a general algorithm based on advanced statistical techniques to better interpret the data. These authors used the developed approach to analyze 18 data sets including mRNA, protein levels, protein-DNA interaction data, and protein-protein interaction data related to galactose utilization in S. cerevisiae (Hwang et al, 2005b) and identified 69 genes that were perturbed significantly in the data sets. Additionally, the analysis suggested that fructose metabolism would be down regulated in the presence of galactose via the downregulation of a hexose transporter, a hypothesis that was experimentally verified through the measurement of corresponding protein levels.…”
Section: Systems-level Data Analysis and Miningmentioning
confidence: 99%